Agrochemicals disrupt multiple endocrine axes in amphibians - Trudeau, Vance L; Thomson, Paisley; Zhang, Wo Su; Reynaud, Stéphane; Navarro-Martin, Laia; Langlois, Valérie S. (Molecular and cellular endocrinology, 2020)
Concern over global amphibian declines and possible links to agrochemical use has led to research on the endocrine disrupting actions of agrochemicals, such as fertilizers, fungicides, insecticides, acaricides, herbicides, metals, and mixtures. Amphibians, like other species, have to partition resources for body maintenance, growth, and reproduction. Recent studies suggest that metabolic impairments induced by endocrine disrupting chemicals, and more particularly agrichemicals, may disrupt physiological constraints associated with these limited resources and could cause deleterious effects on growth and reproduction. Metabolic disruption has hardly been considered for amphibian species following agrichemical exposure. As for metamorphosis, the key thyroid hormone-dependent developmental phase for amphibians, it can either be advanced or delayed by agrichemicals with consequences for juvenile and adult health and survival. While numerous agrichemicals affect anuran sexual development, including sex reversal and intersex in several species, little is known about the mechanisms involved in dysregulation of the sex differentiation processes. Adult anurans display stereotypical male mating calls and female phonotaxis responses leading to successful amplexus and spawning. These are hormone-dependent behaviours at the foundation of reproductive success. Therefore, male vocalizations are highly ecologically-relevant and may be a non-invasive low-cost method for the assessment of endocrine disruption at the population level. While it is clear that agrochemicals disrupt multiple endocrine systems in frogs, very little has been uncovered regarding the molecular and cellular mechanisms at the basis of these actions. This is surprising, given the importance of the frog models to our deep understanding of developmental biology and thyroid hormone action to understand human health. Several agrochemicals were found to have multiple endocrine effects at once (e.g., targeting both the thyroid and gonadal axes); therefore, the assessment of agrochemicals that alter cross-talk between hormonal systems must be further addressed. Given the diversity of life-history traits in Anura, Caudata, and the Gymnophiona, it is essential that studies on endocrine disruption expand to include the lesser known taxa. Research under ecologically-relevant conditions will also be paramount. Closer collaboration between molecular and cellular endocrinologists and ecotoxicologists and ecologists is thus recommended. •We review the endocrine-disrupting actions of typical and atypical agrochemicals in amphibians.•Pesticides, fertilizers and metals all impact aspects of amphibian development, metabolism and reproduction.•Emerging evidence suggests links between multi-levelo endocrine disruption and amphobain population effects